(untitled) (Heritage, 2025)
One of the unique Serbian customs that distinguishes the Serbian people from all other nations, even within the Balkans, is the slava (patron saint celebration). This cultural heritage from Serbia was inscribed in 2014 in the UNESCO Register of Intangible Cultural Heritage. This paper focuses on describing the celebration of slava in the village of Graničane, in northern Kosovo and Metohija, naturally within the broader context of the slava as a phenomenon in Serbia through certain analogies. A detailed study of both the customs and the songs that form an integral part of the slava celebration in Graničane provides a very illustrative example of the uniqueness of each specific locality in regard to all elements of folk tradition. It is of great importance that every folk custom be studied at the level of individual localities due to their specific features, since generalizations could overlook the diversity of Serbian folk traditions, which are most strongly reflected in their richness. The homogeneity of certain traits of Serbian folk tradition makes Kosovo and Metohija especially important, due to geopolitical circumstances that have caused the displacement of a large percentage of the Serbian population. Therefore, such studies are of particular significance for preserving Serbian folk traditions in Kosovo and Metohija. Unfortunately, this may remain one of the rare testimonies of the presence of the Serbian people in the southern province of Serbia, given the political circumstances that have led to the mass displacement of Serbs from many areas in southern Kosovo and Metohija, especially after 1999. Recent events suggest the possibility of a similar fate for other regions and villages of the province, which makes recording the testimonies of the inhabitants from all aspects of research extremely important. This paper is one among such works, showing how in one village in northern Kosovo and Metohija a patron saint’s day is celebrated in a unique way, a celebration that itself is distinctive to the Serbian Orthodox people.